1967
DOI: 10.1042/bj1020748
|View full text |Cite
|
Sign up to set email alerts
|

Influence of organic anions on the liberation of penicillinase from Staphylococcus aureus

Abstract: 1. A further fraction of ;cell-bound exopenicillinase', in addition to that bound ionically to the surface of the cell wall, has been identified in Staphylococcus aureus. 2. Treatment of cells with low concentrations (0.01m) of organic anions liberates part of this exopenicillinase, such liberation being dependent on both time and temperature, but independent of an external supply of energy. 3. Tricarboxylic acids tend to be more effective than dicarboxylic or monocarboxylic, although there are large differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1967
1967
1996
1996

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…This strain, when fully induced, behaves like the constitutive mutant with respect to the liberation properties described (2,3). However, when it was grown in the absence of cloxacillin after treatment with 0.15 M sodium citrate, conditions under which synthesis of all proteins other than penicillinase would be expected to be normal, there was almost no transfer of internally located penicillinase, and the external sites remain nearly devoid of this enzyme ( Table 1).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…This strain, when fully induced, behaves like the constitutive mutant with respect to the liberation properties described (2,3). However, when it was grown in the absence of cloxacillin after treatment with 0.15 M sodium citrate, conditions under which synthesis of all proteins other than penicillinase would be expected to be normal, there was almost no transfer of internally located penicillinase, and the external sites remain nearly devoid of this enzyme ( Table 1).…”
Section: Resultsmentioning
confidence: 96%
“…Cloxacillin was a commercial product of Commonwealth Serum Laboratories, Victoria, Australia. Other materials and methods used were as previously described (2,3).…”
mentioning
confidence: 99%
“…In previous studies of the synthesis and liberation of penicillinase (EC 3.5.2.6) by cells of Staphylococcus aureus (3,4), we showed that there is a fraction of cell-bound penicillinase, comprising up to 40% of the total, which can be liberated by incubation of the cells for short periods at 37 C in 0.15 M sodium citrate. This fraction of cell-bound exopenicillinase is replenished only under conditions permitting de novo penicillinase synthesis and is the most recently synthesized enzyme (5).…”
mentioning
confidence: 91%
“…Incubation mixtures for incorporation of radioactive precursors were the same as induction mixtures (7) with the omission of inducer, but with the following additions: for protein synthesis, 0.1 mg of amino acid mixture (4) containing 0.1 MCi of "4C-protein hydrolysate; for nucleic acid synthesis, 0.1 ml of 3 mM "C-uracil (0.1 MCi/smol) or 0.1 ml of 3 mM 3H-thymidine (16.7 ACi/umol); for lipid synthesis, 0.1 ml of 25 mM '4C-sodium acetate (1 IACi/umol). Radioactive compounds were added after temperature equilibration at 37 C. At the end of the incubation period samples for the measurement of radioactivity incorporated into nucleic acids and proteins were treated as previously described (3,5) and counted in a Nuclear-Chicago gas-flow counter.…”
mentioning
confidence: 99%